'I ain't stupid, I just don't like school': a 'needs' based argument for children's educational provision in custody. (21st April 2022) - Paterson-Young, Claire; Bajwa-Patel, Meanu; Hazenberg, Richard
ABSTRACT: Whilst the number of children in custody declines, the complex needs of many of them have increased. A review of the youth justice system stated that education needs to be the central pillar in preventing offending. Research suggests that education fails children, by prioritising reputation and the standards agenda over providing care and education that meets individual needs (Runswick-Cole. 2011. "Time to End the Bias Towards Inclusion." British Journal of Special Education 38 (3): 11). This paper explores this failure for children prior to and in custody itself, and relates this to a theoretical model that combines children's need and self-efficacy. It suggests that until children are guaranteed an environment where their basic needs are met, there is little hope of either education or training helping them to access a life free from crime, whatever other policy changes in custody are implemented. This research shows that current provisions, for children in custody, fail to support children's needs around safety, belonging and self-esteem. Thus, it is no surprise that children in Secure Training Centres fail to self-actualise their educational abilities, as they lack the self-efficacy to successfully engage with education.